Evaluating the protective effectiveness and risk factors of ursodeoxycholic acid on COVID-19 among outpatients - Li, Di; Fang, Qimei; Chen, Zhiwei; Tang, Jing; Tang, Haoling; Cai, Nan; Qiu, Ke; Zhu, Mingyang; Yang, Xuemei; Yang, Lu; Yang, Yujie; Huang, Yong; et al. (Frontiers in Pharmacology, 2024)
This study aimed to assess the chemopreventive effect of ursodeoxycholic acid (UDCA) against COVID-19 and to analyze infection risk factors, symptoms, and recovery in outpatients with UDCA exposure.The study enrolled outpatients prescribed UDCA from the Second Affiliated Hospital of Chongqing Medical University, China, between July 1, 2022, and December 31, 2022. Data on demographics, comorbidities, and drug combinations were collected using electronic medical records. COVID-19 infection, symptoms, severity, prognosis, vaccinations, and UDCA administration were surveyed by telephone interviews. UDCA non-users served as controls and were matched in a 1:2 ratio with UDCA users using propensity score matching with the nearest neighbor algorithm. Infection rates, symptomatology, severity, and prognosis were compared between matched and control cohorts, and risk factors and infection and recovery symptoms were analyzed in UDCA-exposed outpatients.UDCA-exposed outpatients (n=778, 74.8%) and matched UDCA users (n=95, 74.2%) showed significantly lower SARS-CoV-2 infection rates than control patients (n=59, 92.2%) (p<0.05).The matched UDCA group exhibited substantially lower fever, cough, sore throat, and fatigue rates than controls (p<0.05). Participants with UDCA exposure generally experienced mild symptoms, while those without UDCA had moderate symptoms. The matched UDCA group also had significantly shorter durations of fever and cough (p<0.05). Risk factors such as age over 60, less than one month of UDCA administration, diabetes mellitus, and coronary artery disease significantly increased SARS-CoV-2 infection rates (p<0.05), while smoking led to a decrease (p<0.05). Hypertension was associated with a prolonged COVID-19 recovery (p<0.05), while smoking, vaccination, and fatty liver disease were associated with shorter recovery periods (p<0.05). The main symptoms in the full UDCA cohort were fever, cough, and sore throat, with fatigue, cough, and hyposthenia being the most persistent.UDCA demonstrated chemopreventive effect against SARS-CoV-2 in outpatients by significantly reducing infection incidence and mitigating COVID-19 symptoms, severity, and recovery duration. Old age, short UDCA course, and comorbidities such as diabetes mellitus and CAD increased infection rates, while hypertension prolonged recovery. Smoking, vaccination, and fatty liver disease reduced infection rates and shortened recovery. UDCA had minimal impact on symptom types. Larger and longer-term clinical studies are needed further to assess UDCA's effectiveness in COVID-19 prevention or treatment.